Assessing Risk in Postal Services – The Role of Users’ Subjective Security Perceptions - BINIČKI, Marijan; KLJAK, Tomislav; ŠKORPUT, Pero; BLAŠKOVIĆ-ZAVADA, Jasna (Promet - Traffic&Transportation, 2026)
The paper explores the possibility and necessity of incorporating users’ subjective perceptions of safety into risk assessments. The survey has been done as a statistical analysis of questionnaires fulfilled by Croatian Post (HP – Hrvatska pošta) users, highlighting their perceptions of various aspects and suggestions about physical security, transaction security and postal items handling. This way, subjective perception is offered as a base for further definition or calibration of already existing variables used for risk assessment calculations. At the same time, this aspect of monitoring and analysing postal services offers the possibility of assessing service quality not only based on transit time or the number of complaints, as is currently the case, but also through the function of perceived safety. The results show a high level of user confidence in their interactions with the postal system, although there is significant room and need for improvement in procedures when an unwanted incident occurs. The survey results provide a comprehensive overview of user perceptions and areas for improvement in the security and protection of postal services.